2020
DOI: 10.4085/1062-6050-0182.19
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of a Novel Peer Concussion-Education Program for Collegiate Athletes

Abstract: Context The National Collegiate Athletic Association and US Department of Defense have called for educational programs to change the culture of concussion reporting, increase reporting behavior, and enhance the safety of players and service members. Objective To evaluate the effects of a novel peer concussion-education program (PCEP) in changing knowledge, attitudes, and norms about concussion reporting among collegiate stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 26 publications
(41 reference statements)
0
23
0
Order By: Relevance
“…The effectiveness of the PCEP was investigated during a national randomized controlled trial, and the results are reported in ''Randomized Controlled Trial of a Novel Peer Concussion Education Program in Collegiate Athletes. 41…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the PCEP was investigated during a national randomized controlled trial, and the results are reported in ''Randomized Controlled Trial of a Novel Peer Concussion Education Program in Collegiate Athletes. 41…”
Section: Discussionmentioning
confidence: 99%
“…Participation in the study was voluntary. For more complete details of the RCT, see Kneavel et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…An adapted version of a Theory of Planned Behavior questionnaire (Kneavel et al, 2020) contained subscales to measure (a) intention to report concussion, (b) direct attitudes, (c) direct perceived behavioral control, (d) indirect attitude, and (e) indirect perceived behavioral control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations